Controlled Trim-Blasting Model to Improve Stability and Reduce Vibrations at a Production Gallery of the San Ignacio de Morococha S.A.A. Mining Company - Camallanqui-Alborque, C. (2019)
This paper presents a blasting method called controlled trim blasting, in which the rock mass of an unstable gallery where high levels of vibration have been detected is analyzed. This methodology comprises a drilling mesh with two-contour gallery assessment, producing its drilling machines and determining the type of explosive used and burden and spacing, which will be detonated after the internal blasting. Further, the internal blasting will possess its drilling machines, burden, spacing, and a second type of explosive. The separation of the gallery into smaller parts will improve the blasting, as verified in the recorded simulation. In addition, the rock-mass stability improves because the explosives used in the perimeter of the gallery are low-power with mild detonation pressure, which does not generate high levels of vibration. This is a practical and efficient method in areas where the rock mass is not good or there is a mixture of rock types.